Eficacia del ejercicio físico sobre la calidad de vida en fibromialgia: Meta-análisis de ensayos clínicos (2023)
Introduction: Physical activity is effective in reducing fatigue, anxiety and depression in patients with fibromyalgia, and to improve the quality of life. Objective: To evaluate the efficacy of physical activity in improving the quality of life of people with fibromyalgia, 2004-2014. Methods: Meta-analysis of controlled clinical trials evaluating the efficacy of physical activity on the FIQ (Fibromyalgia Impact Questionnaire) and MOSSF-36 (Medical Outcome Study Short Form) scores, with 18 search strategies in four multidisciplinary databases. A protocol that containing criteria for inclusion, exclusion, assessment of methodological quality and extraction of information, were applied by two researchers to ensure reproducibility. Random effects meta-analysis, sensitivity analysis, DerSimonian-Lairds heterogeneity and publication bias with Begg test was performed. Results: 10 studies were included, the most in Spain and Brazil; 203 patients with intervention and 238 in the control group. The meta-analysis showed homogeneity in the FIQ and MOSSF-36 scores between groups, prior to the implementation of the intervention; after the application of intervention were identified difference of 14.9 points (95% C110.3; 19.5) in the FIQ and 2.0 on the MOSSF-36, was best in the group that received exercise therapy. Conclusion: The major efficacy of regular physical exercise is evident, compared with conventional treatment, to improve the quality of life of patients with fibromyalgia. Measuring the quality of life as a primary outcome in clinical trials should be performed with the FIQ.